Engineered mesoporous silica-based nanoparticles as smart chemotherapy nanodevice for bortezomib administration. (12th December 2022) - De Santo, M.; Giovinazzo, A.; Fava, M.; Mazzotta, E.; De Napoli, I. E.; Greco, M.; Comandé, A.; Nigro, A.; Argurio, P.; Perrotta, I.; Davoli, M.; Tagarelli, A.; et al.
Abstract : Engineered mesoporous silica-based nanostructures for selective and pH-sensitive release of the anticancer drug bortezomib. The developed "smart chemotherapy" showed higher efficacy in vivo compared to traditional free bortezomib administration. Abstract : Adverse reactions, toxicity, and poor compliance from patients still represent major challenges for conventional chemotherapy treatments. Localized drug delivery would ideally improve therapeutic efficacy, minimizing the side effects. An MSU-type mesoporous silica-based nanodevice (FOL-MSN-BTZ), able to selectively deliver the antineoplastic drug bortezomib (BTZ) to folate receptor over-expressing multiple myeloma (FR+ MM) cells is described. The receptor-specific ligand, folic acid, grafted on the external surface of the nanosystem, allows tumor recognition and cell internalization, while BTZ, mainly linked to the pore internal surface through a covalent pH-sensitive bond, is released in an acidic tumor environment. A detailed investigation showed that only the fine balancing of different functionalities of the nanodevice around the external and internal surfaces of MSN particles shows the absence of toxicity towards healthy cells in vitro and negligible BTZ-release at physiological pH, which are suitable features for applicative purposes in the engineering of therapies. After complete characterization in vitro, an accurate suspendability assessment, which considered the sedimentation process that reduces the particle amount and, consequently, drug content in the suspensions, allowed the development of an injectable formulation of FOL-MSN-BTZ that showed higher antitumor efficacy and an overall tendency to lower toxicity in a MM mice model compared to the conventional bortezomib chemotherapy.